Targeting the CINful genome: Strategies to overcome tumor heterogeneity. (October 2019) - Cunningham, Chelsea E.; MacAuley, Mackenzie J.; Yadav, Garima; Vizeacoumar, Frederick S.; Freywald, Andrew; Vizeacoumar, Franco J.
Abstract: Genomic instability, and more specifically chromosomal instability (CIN), arises from a number of processes that are defective in cancer, such as aberrant mitotic cell division, replication stress, defective DNA damage repair, and ineffective telomere maintenance. CIN is an emerging hallmark of cancer that contributes to tumor heterogeneity through increased rates of genetic alterations. As genetic heterogeneity within a single tumor and between tumors is a key challenge leading to treatment failures, this brings to question, whether therapeutic approaches should aim at the genetic diversity or a specific mutation present within these tumors. Answering this question will determine the future of personalized targeted therapies. Here we discuss, how the genetic diversity associated with CIN in tumor cells can be used as a therapeutic advantage and targeted by exploiting the genetic concepts of synthetic lethality and synthetic dosage lethality. Given that a number of CIN-related pathways work together to fix the DNA damage within our genome and ensure proper segregation of chromosomes, we specifically focus on the genetic interactions amongst these pathways and their potential therapeutic applicability in cancer. We also discuss, how tumor genetic heterogeneity can be targeted in emerging immunotherapeutic approaches.